Keterkaitan Akuntabilitas, Motivasi, Pendidikan terhadap Kinerja Dengan Komitmen Organisasi sebagai Variabel Mediasi (Studi pada Pengelolaan Keuangan di SKPD Provinsi Bengkulu) - Kamelia Astuty; Rini Indriani; Nila Aprilia (UNIVED Press, 2022)
The purpose of this study was to analyze the relationship between accountability, motivation, education on performance in Bengkulu Province Financial Management and to analyze the relationship between performance and organizational commitment in Bengkulu Province financial management. Financial management is all fields of work that use expertise in the accounting field, including public accountants, internal accountants working in industrial, financial or trade companies, accountants working in the government, and accountants as educators. The task of an accountant is to perform accounting tasks such as financial statement analysis, is responsible for reporting financial results for both the company and the government. This research uses quantitative methods with a total of 195 respondents. Research Using Structural Equation Modeling (SEM) using AMOS software version 23.0.